2021
DOI: 10.1002/eco.2352
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence structure and longitudinal velocity distribution of open channel flows with reedy emergent vegetation

Abstract: The vertical distribution of longitudinal velocity and the turbulence structure of open channel flows with natural‐like reedy emergent vegetation were investigated in this study. The natural‐like reedy vegetation consisted of a basal stem and flexible blades with shape and reconfiguration behaviour comparable with those found in actual riparian areas. The 3D velocity field was measured using an acoustic Doppler velocimeter. The vertically non‐uniform distribution of the frontal area could dramatically affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…On the one hand, the vegetation may considerably increase flow resistance, slowing down the flow and raising the water levels, so increasing the risk of floods. On the other hand, by changing in velocity distribution and turbulent structures in vegetated channels (Li et al, 2015;Nikora et al, 2013;Wang et al, 2022;Yang et al, 2019), vegetation promotes sediment deposition (Wu and He, 2009), reduces bed erosion and increases bank stability (Vargas-Luna et al, 2016). Furthermore, vegetation is known to provide habitats for aquatic and terrestrial wildlife, beautify the environment, and permeate pollutants (Huai et al, 2018;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the vegetation may considerably increase flow resistance, slowing down the flow and raising the water levels, so increasing the risk of floods. On the other hand, by changing in velocity distribution and turbulent structures in vegetated channels (Li et al, 2015;Nikora et al, 2013;Wang et al, 2022;Yang et al, 2019), vegetation promotes sediment deposition (Wu and He, 2009), reduces bed erosion and increases bank stability (Vargas-Luna et al, 2016). Furthermore, vegetation is known to provide habitats for aquatic and terrestrial wildlife, beautify the environment, and permeate pollutants (Huai et al, 2018;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Flume experiments based on model vegetation, which is simulated by cylinder or strip arrays, have been employed for two decades (Ben Meftah & Mossa, 2016; Ghisalberti & Nepf, 2004; Huai et al, 2015; Liu et al, 2020; Nepf & Vivoni, 2000; Nezu & Onitsuka, 2001; Shan et al, 2020; Wang, Liu, et al, 2021; Yan et al, 2015; Yan et al, 2016; Yan et al, 2020). By changing the flow depth, submerged and emergent vegetation canopies can be modelled (Chang et al, 2020; Li et al, 2014; Yan et al, 2016), and by changing the obstruction ratio of the flume, partially distributed and fully distributed vegetation canopies can be modelled (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic plants play an important role in the beauty, ecological restoration, and flood controls in rivers, canals, and also impact the nutrients transmission, flow structures, and turbulence (Tsujimoto, 1999; Wang et al, 2021). Vegetation provides habitats for aquatic lives, to increase bank stability, reduce erosion, decrease turbidity, reduce floods, and permeate pollutants (Bennett et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, the flow velocity fluctuates more significantly; average flow velocity is higher when vegetation is parallel than staggered, and the averaged flow velocity is higher when vegetation is sparse than dense in upstream of vegetation area. Wang et al (2021) found that the flow velocity under the presence of emergent vegetation can be decreased. It is of great significance in flood control of rivers.…”
Section: Introductionmentioning
confidence: 99%